2007
DOI: 10.1007/s10620-007-0095-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Function of Dendritic Cells in Esophageal Cancer

Abstract: Esophageal cancer is one of the frequently occurring malignant cancers. The current therapy, including surgery, chemotherapy, radiotherapy, or a combination, is only to palliate the symptoms; overall the prognosis is poor. The immunotherapy of dendritic cells for esophageal cancer is a valuable method. Dendritic cells existing in the esophageal tissues play an important role in the host's immunosurveillance against cancer as the professional antigen-presenting cells. This review concerns the immunology of dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…[44][45][46] The importance of dendritic cells in immune surveillance suggests that infiltration of dendritic cells into tumors should have prognostic significance, [44][45][46] but this has not been a consistent finding. An increased infiltration of dendritic cells into esophageal squamous cell carcinoma and hepatocellular carcinoma is associated with good prognosis for patients with such cancers, [47][48][49] but there was no significant association with prognosis in two studies of patients with renal cell carcinoma, for example. [50][51][52] As an explanation for these variable findings, Mailliard et al 53 suggest that infiltrating dendritic cells might promote T-cell survival or death, depending on their maturation stage and function.…”
Section: Discussionmentioning
confidence: 96%
“…[44][45][46] The importance of dendritic cells in immune surveillance suggests that infiltration of dendritic cells into tumors should have prognostic significance, [44][45][46] but this has not been a consistent finding. An increased infiltration of dendritic cells into esophageal squamous cell carcinoma and hepatocellular carcinoma is associated with good prognosis for patients with such cancers, [47][48][49] but there was no significant association with prognosis in two studies of patients with renal cell carcinoma, for example. [50][51][52] As an explanation for these variable findings, Mailliard et al 53 suggest that infiltrating dendritic cells might promote T-cell survival or death, depending on their maturation stage and function.…”
Section: Discussionmentioning
confidence: 96%
“…In EC, it is also reported that tumor microenvironment has a close relationship with tumor growth. The cells, including NK cells, T cells, B cells, plasma cells, monocytes, macrophages, dendritic cells, mast cells, eosinophils, and neutrophils, have all been reported to have exhibited significant association with EC treatment [7,10,[25][26][27][28][29][30][31][32]. The elevation or reduction of these different types of TIICs in tumor microenvironment is commonly associated with poor prognosis of EC.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, no side effects were seen against normal cells, meaning that tolerance towards normal antigens was maintained [76]. The importance of the role of DCs in esophageal squamous cell carcinoma has been previously discussed by Yang et al [77]. Several experimental immunotherapies for esophageal cancer, such as cancer vaccine by fusions of esophageal cancer cells with DCs, DC vaccines pulsed with MAGE-3, MAGE-4, or SART-1 peptide, have been explored.…”
Section: Results From Clinical Trials Using DC Immunotherapymentioning
confidence: 99%